SOSIALISASI PENGISIAN INVOICE (TAGIHAN BARANG) BAGI IBU-IBU UMKM DI KAWASAN RW.08 SUNTER AGUNG JAKARTA UTARA - Susanti Ningsih; Koerniawan Hidajat (LPPM Universitas Bina Bangsa, 2024)
The aim of this research is to provide structured socialization about filling out invoices to MSME women in the RW 08 Sunter Agung area, North Jakarta. This socialization aims to increase participants' understanding and practical skills in preparing invoices correctly and efficiently in their business activities. Through a structured approach and supported by relevant material, it is hoped that participants can gain better knowledge about the concept of invoices, the information that must be included in an invoice, and how to practically prepare invoices in accordance with applicable statutory requirements. By providing quality outreach, it is hoped that MSME mothers can optimize their financial management, strengthen relationships with customers, and increase the operational efficiency of their business. This socialization also aims to help participants avoid potential errors in filling out invoices which could have a negative impact on the company's cash flow and relationships with customers. In addition, by increasing understanding and practical skills in filling out invoices, it is hoped that MSME women can face business challenges more confidently and effectively, and obtain long-term benefits in improving their overall business performance